Ambivalence in TikTok: lifelong learning and security risks coexisting - Castillejos López, Berenice (IE Revista de Investigación Educativa de la REDIECH, 2021)
The purpose of this essay is to analyze the way in which TitTok contributes to lifelong learning, as well as to assess the security risks generated when using it. Its reflection is based on two questions: How does TikTok promote lifelong learning? What are the risks to which users are exposed? The duality presented by this short video platform invites us to weigh the good and bad aspects of its use. On the one hand, it is a tool that can contribute to lifelong learning; on the other, the security problems that result in the handling of data, harmful content, fake users, the high exposure of personal life, as well as the sensation produced by the scrolling of the videos. Social media cannot be demonized; the important thing is to learn to use them correctly and without dependencies. The digital diet should not be missing in the planning of the use of this application, as well as digital security skills.